The use of The Million's Show as learning methodology in the teaching of work engineering subject (International Journal of Geoscience, Engineering and Technology, 2024)
Currently, with the technological advances, it can be noticed that the use of different methodologies of applied learning objects, are capable to attract students in a fun and interactive ways, so they can learn, test their knowledge, and put into practice the knowledge that was taught in the subject of work engineering. This article was based on the famous Million's Show, which has as the main goal, to be a game of individual questions and answers, which the player must correctly answer each question to reach the end of the game and win. This game was made in the Learningapps website, which is a tool capable of easily editing the game’s contents, been able of making the changes inside the website itself.